CLINICAL APPROACH TO ORAL PAPILLOMATOSIS IN CATS: A CASE STUDY - Viastika, Yanita Mutiaraning; Decline, Vega; Rizky, Asri; Pratiwi, Retno Anggie; Wibowo, Sarwo Edy (VITEK : Bidang Kedokteran Hewan, 2024)
Papilloma refers to the abnormal growth of tissue in the form of tumors or warts. The clinical signs of oral papillomatosis include lesions or masses that develop inside the oral cavity. Oral papillomatosis in cats is caused by Canine Papillomavirus (CPV). The papillomavirus induces tumors by infecting cells through wounds. The purpose of this report is to describe the diagnosis and management of oral papillomatosis in a mixed domestic cat at the Yogyakarta Animal Clinic. Diagnosis of papillomatosis can be made based on visible clinical signs and confirmed through cytological examination of the tumor mass. Management of oral papillomatosis involves the surgical removal of the tumor mass along with the surrounding tissue. Postoperative therapy includes the administration of antibiotics (Cefixime®), anti-inflammatory drugs (Methylprednisolone®), and antifungal agents (Candistatin®).